The relationship between leptin and resistin levels and parameters of the ambulatory blood pressure monitoring in patients with type 2 diabetes and arterial hypertension - Urbanovych A.M. (Medičnì Perspektivi, 2015)
To explore the relationship between leptin and resistin content in plasma and parameters of ambulatory blood pressure monitoring (ABPM) in patients with diabetes mellitus (DM) type 2 and arterial hypertension (AH) I and II degree and without hypertension. The study involved 137 patients with type 2 diabetes with hypertension I and II degree and without hypertension (72 women and 65 men). Patients with type 2 DM and AH were 1st group (n=51, mean age=53,32±0,77, BMI=32,14±0,78 kg/m2), and patients with type 2 DM without AH - 2nd group (n=86, mean age=52,79±0,69, BMI=30,31±0,62 kg/m2). Control group consisted of 32 practically healthy individuals, including 16 women and 16 men (mean age=51,00±0,97, BMI=30,77±1,17 kg/m2). The groups were comparable by age and BMI (P>0.05). All patients underwent clinical and laboratory examination and ABPM. The level of leptin in the blood plasma of patients in two groups and the control one was not statistically different (p>0.05). Instead, resistin content was the highest in patients with type 2 DM and AH, the lowest – in the control group (4,51±0,34 Е 2,64±0,20 ng/ml, p=0.0007); also differed significantly in the 1st and 2nd groups of patients (p=0.0009). The distribution of patients depending on the daily profile of AH (Dipper, Non-dipper, Night-peaker) found no significant changes in the contents of leptin in patients with type 2 DM with AH or without AH. Resistin level was significantly higher in all groups of patients with type 2 DM and AH with different types of daily profile as compared to the groups without AH (p<0.05). In the group of patients with type 2 DM and AH changes in levels of resistin differed significantly in non-dipper and night-peaker groups (p=0.01). Relationship between leptin levels in plasma and ABPM parameters in patients with type 2 diabetes were not set. Instead, resistin levels in blood plasma can be considered as a prognostic marker of cardiovascular disease, including hypertension, in patients with type 2 diabetes.